Cultural Commodification in the Bau Nyale Tradition in Sasak Community - Hablun Ilhami; Moh Soehadha (UIN Sjech M. Djamil Djambek Bukittinggi, 2023)
Today's culture or tradition is filled with cultural values or local wisdom and has economic and political content. It causes the opening of space for cultural capitalization that prioritizes selling or exchanging values and not using values. The study aims to explore the cultural commodification that occurs in the Bau Nyale tradition in the Sasak NTB community, including the existence of the Bau Nyale tradition, the commodification of Bau Nyale, to the value transformation and shifting in the Bau Nyale tradition in the Sasak NTB community. This study is qualitative research with primary data sources, namely community leaders such as Adat and the Sasak people in general. The data obtained through interviews, books, and articles are then interpreted using the commodity approach of Karl Marx. The analysis results show that the Bau Nyale tradition in the Sasak community today is not just a tradition of catching Nyale (sea worms) for the Sasak people. More than that, the Bau Nyale tradition has various dimensions and goals, including economics. In this case, Bau Nyale has become a secondary activity as an activity or tradition that follows the primary activity, namely economic activity. The commodification that occurs in the Bau Nyale tradition in the Sasak community causes a shift in orientation and even raises social problems such as gambling, fights, and even murder cases.